Flavour development of East Midlands cheeses and evaluation of flavour producing microorganisms in a small scale real-cheese model - Whiley, Henry (2013)
Stilton is a blue-veined cheese made from pasteurised milk. The diversity of the microflora found within the cheese helps develop the unique flavour and aroma of Stilton compared to other blue cheese. However, this flora is not controlled and so product may be variable. A small-scale cheese model was developed to allow examination of the effect of different microflora on flavour production in a controlled way. Texture analysis, water activity and viable count of the cheese models were compared to commercial cheeses in order to optimise the model. The final model had the hardness of Danish Blue and the water activity of Stilton. The growth of lactic acid bacteria through the cheese making process was monitored and showed a characteristic reduction after salting. Changes in total aerobic count and yeast and moulds after salt addition and handling showed the ease with which the cheese can become contaminated with external flora such as yeasts and moulds even under aseptically manipulated conditions. Solid Phase Microextraction Gas Chromatography Mass-Spectrometry was used to evaluate the flavour volatiles produced when milk and cheese were inoculated with different microorganisms. Some yeast species such as Trichosporon beigleii inhibited the metabolism of P. roqueforti within the models, where as others such as Debaryomyces hansenii aided the metabolism of compounds in the models to develop different flavour volatiles. Overall a small-scale blue cheese model was produced and can be used to understand the role of different organisms in the development of the flavour and aroma of blue cheeses in the future.